NEW ASPECTS OF ELECTROCHEMICAL OXIDATION OF ALUMINUM - Крюкова, Олена; Бутенко, Ангеліна (Modern engineering and innovative technologies, 2023)
Purpose: to conduct a literary review of foreign and native sources of information on the process of anodizing aluminum and its alloys.Methodology: analysis of open literary sources by the method of comparative characteristics.Findings: it was found th